Novel metallic separator coupled composite phase change material passive thermal design for large format prismatic battery pack. (February 2023) - Talele, Virendra; Patil, Mahesh Suresh; Panchal, Satyam; Fraser, Roydon; Fowler, Michael; Gunti, Seeta Ratnam
Abstract: To enhance the lithium-ion battery pack's operating performance while it is continuously used at varying charge rate and higher ambient temperatures, the current research proposes a thermal management system composed of a phase change material with a passive metallic connection. Along with constant charge rate of 1C, 2C and 3C rate, battery pack also investigated at harshest 4C rate condition, to check its thermal performance. In total, three configurations are investigated: configuration 1 has no passive cooling arrangement, configuration 2introduces a passive thermal design with a phase change material submerged cooling technique that includes paraffin wax and extended graphene composite phase change material, and configuration 3is a proposed improved thermal design in which a graphene-enhanced high thermal conductive metallic separator is coupled at the PCM wall to increase PCM temperature delay efficiency. A phenomenon of inefficient thermal performance is observed for typical pure PCM form due to its lower thermal conductivity and heat transfer rate, resulting in a loss of capacity to cause temperature delay effect in battery pack. In proposed improved model of having metallic separator at wall of PCM results shows, none of the case had exceeded effective battery temperature limit of 55°C and liquid fraction rate of PCM and EG CPCM remained below liquidious point which allows it to deliver more temperature delay effect. Comparative performance study between paraffin wax PCM and EG CPCM suggest EG CPCM is able to provide more delay effect due to its thermophysical property advantage of higher thermal conductivity and greater heat transfer performance. Highlights: A comparative battery thermal performance study between paraffin wax and EG PCM has performed. The lack of thermal performance is detected over conventional PCM cooling strategy at higher charge rate. To increase temperature delay effect a novel metallic separator coupled PCM (MSCP) is proposed Thermal performance of MSCP is verified under dynamic charge rates with different ambient condition. MSCP helps PCM to increase latent cooling effect by delaying temperature threshold limit.